Vacância residencial nos centros históricos urbanos: O caso de S\~ao Paulo - Vanessa Gapriotti Nadalin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– S\~ao Paulo's metropolitan area is one of the largest urban spaces in the world. As it ha ppens with any other large metropolitan area, understanding its structure, problems and dynamics is not a simple task. The structure of cities has been studied by urban economics ever since von Thünen's land use theory was adapted to urban contexts. Research on property and housing markets have followed a related but different approach. On the one hand, housing markets have been modeled with emphasis on the specific features of properties such as durability, heterogeneity, and construction costs. On the other hand, research on real estate finance has been developing and applying a variety of valuation methods, focusing on the supply and demand adjusting mechanisms and considering properties as assets. These three areas of investigation have not always been connected in a systematic manner. Yet, we argue that there is a case for integrating them due to their intrinsic spatial dimension. [...]
Keywords: R31; 330; vacancy rates; housing; city center; hedonic modeling